(untitled) (Journal of Paediatric Surgeons of Bangladesh, 2014)
This prospective, comparative and interventional study was conducted in Bangabandu Sheikh Mujib medical university in Dhaka and Center Point Hospital pvt .ltd in chittagong to evaluate advantage of using readily absorbable synthetic suture material IRPG 910 over non absorbable polypropylene in repair of cleft lip between time period of January 2003 to May 2004 in fulfillment of final part MS degree in pediatric surgery. A total of 26 patients with cleft lip (with or without cleft palate) who underwent operative procedure were included in this study. All the patients between the age of 3 months to 10 years having unilateral cleft lip with or without cleft palate were included while those with grossly deformed face or those associated with major anomaly were excluded. Patients were divided into two groups, one group with 12(46%) as cases were IRPG 910 was used as a skin closure material and one group with 14(56%) as control group where polypropylene was used. In all the cases Milards procedure was used except for one with central defect where linear closure was done, at the end of the study it is justified that IRPG 910 is as good as polypropylene as a suture material of choice in repair ofcleft lip considering every pros and cons of both suturematerials namely cost effectiveness, patientcompliance, post operative complication and out come. The most beneficial thing about using IRPG 910 over polypropylene was that it can avoid second anesthesia for stitch removal. DOI: http://dx.doi.org/10.3329/jpsb.v1i1.19451